Posted by **James** on Tuesday, September 17, 2013 at 10:17am.

Let P=(cosA sinA)

(sinA cosA)

Q=(cosB sinA)

(sinB cosA) show that

PQ=(cosA(A-B) sin(A B))

(sinA(A B) cos(A-B))

## Answer This Question

## Related Questions

- Maths - Hi, can someone give me the answer to this question: secA-tanA=1/4. Find...
- trig - How to do this one? (sina/1-cosa) + (1-cosa/sina) = Also, wanted to ask ...
- trig - Please help me how to do this: 1) 1 + sina*cosa / (cosa + sina)^2 = 2) ...
- trig - I need to count this: a) 1-tg^2a/1+ctg^2a, when sina =2/3 b) 1-tg^2a/1-...
- Maths, Divine International Public School - If 15Cot=8, find (1+SinA)(1-SinA)/(1...
- trig - Establish the following identity: CosA/1-TanA + SinA/1-CotA = CosA-SinA
- maths(trigonometry) - prove that sinA-cosA+1/sinA+cosA-1=1/secA-tanA
- trig - Prove : (sinA-cosA+1)/(sinA+cosA-1) = (1+sinA)/cosA
- trigonometry - Prove : 1 + Sin2A/ Cos2A = CosA + SinA / CosA- SinA
- trig - prove that :cosA-sinA+1/cosA+sinA-1=cosecA+cotA

More Related Questions